2021
DOI: 10.1371/journal.pone.0251280
|View full text |Cite
|
Sign up to set email alerts
|

Middle ratings rise regardless of grammatical construction: Testing syntactic variability in a repeated exposure paradigm

Abstract: People perceive sentences more favourably after hearing or reading them many times. A prominent approach in linguistic theory argues that these types of exposure effects (satiation effects) show direct evidence of a generative approach to linguistic knowledge: only some sentences improve under repeated exposure, and which sentences do improve can be predicted by a model of linguistic competence that yields natural syntactic classes. However, replications of the original findings have been inconsistent, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Judging from their experimental results with the standardized fillers, Gerbrich et al (2019, p. 309) conclude that there may be even more distinguishable levels of well-formedness. Note that the E-level is still interpretable, but highly unnatural; it is possible to add a further level with low interpretability, as for example in the adaptation of the standard fillers in Brown et al (2021). Brown et al (2021, p. 10) refer to this as a "clearly ungrammatical level" with examplessuch as The ink was for spilled that are considered both unacceptable and uninterpretable.…”
Section: The Use Of Standardized Fillersmentioning
confidence: 99%
“…Judging from their experimental results with the standardized fillers, Gerbrich et al (2019, p. 309) conclude that there may be even more distinguishable levels of well-formedness. Note that the E-level is still interpretable, but highly unnatural; it is possible to add a further level with low interpretability, as for example in the adaptation of the standard fillers in Brown et al (2021). Brown et al (2021, p. 10) refer to this as a "clearly ungrammatical level" with examplessuch as The ink was for spilled that are considered both unacceptable and uninterpretable.…”
Section: The Use Of Standardized Fillersmentioning
confidence: 99%
“…Recent studies found that acceptability judgments are affected by a pervasive phenomenon called syntactic satiation, or simply satiation: participants in acceptability rating experiments rate degraded sentences as increasingly acceptable as they see more instances of such sentences (Braze, 2002;Hiramatsu, 2001;Snyder, 2000, inter alia). The satiation effect has recently drawn much attention, and there is an abundance of experimental studies testing whether various unacceptable sentence types satiate in English (Braze, 2002;Chaves & Dery, 2014Crawford, 2012;Do & Kaiser, 2017;Francom, 2009;Goodall, 2011;Hiramatsu, 2001;Lu et al, 2021Lu et al, , 2022Snyder, 2000Snyder, , 2022aSprouse, 2009) and other languages (Abugharsa, 2016;Brown et al, 2021;Goodall, 2011;Myers, 2012;Sommer, 2022). However, the satiation literature is replete with mixed empirical findings and non-replications regarding which sentence types are affected by satiation (see Snyder, 2022b, for a review), thus hindering the development of a coherent theoretical picture.…”
Section: Introductionmentioning
confidence: 99%
“…14 Due to the decision to focus on satiation studies looking at the same sentence types examined in (Snyder 2000), some work on another sentence types, namely superiority violations, will receive only the following remarks. Briefly, Hofmeister et al (2013) for English and Brown et al (2021) for both German and English reported increased acceptance of superiority violations after multiple judgments. Yet, there are some reasons to be skeptical that their findings resulted from "syntactic satiation" in the sense intended here-in other words, from the type of satiation reported anecdotally among professional linguists.…”
mentioning
confidence: 99%